Copyright Law In Malaysia: Does The Balance Hold? - Khaw, Lake Tee (Journal of Malaysian and Comparative Law, 2019)
If we were to take a very simplistic view of the copyright landscape in Malaysia, we could be forgiven for surmising that Malaysia is a country of suppliers, retailers and consumers of pirate VCDs and DVDs of music and films, and software; and that copyright law basically deals with criminal activities. We also could be forgiven for thinking that the question of balance under our copyright law is a non-issue. Indeed, copyright owners may feel, given the proliferation of pirated products, the balance is heavily stacked against them; while consumers may think that enforcement activities have unfairly prejudiced or frustrated their access to cheap and ready supplies for copyright works, and conclude that the balance is more definitely tilted in favour of the copyright owners. For where else is the Government more involved in the protection of a form of private property right, the owners of which are mainly foreign? Granted there is an overemphasis on the portrayal of copyright infringement as criminal activities, thus giving rise to perception, rightly or wrongly, that copyright law is enforced by the State on behalf of the copyright owners. However, while it is tempting to argue that this underscores a leaning towards the copyright owner, it should be made clear that the enforcement of the criminal provisions is quite different from the balancing act that copyright law does.